Impaired Self-Monitoring of Inner Speech in Schizophrenia Patients with Verbal Hallucinations and in Non-clinical Individuals Prone to Hallucinations - Brébion, Gildas; Stephan-Otto, Christian; Ochoa, Susana; Roca, Mercedes; Nieto, Lourdes; Usall, Judith (Frontiers in Psychology, 2016)
Background: Previous research has shown that various memory errors reflecting failure in the self-monitoring of speech were associated with auditory/verbal hallucinations in schizophrenia patients and with proneness to hallucinations in non-clinical individuals. Method: We administered to 57 schizophrenia patients and 60 healthy participants a verbal memory task involving free recall and recognition of lists of words with different structures (high-frequency, low-frequency, and semantically-organisable words). Extra-list intrusions in free recall were tallied, and the response bias reflecting tendency to make false recognitions of non-presented words was computed for each list. Results: In the male patient subsample, extra-list intrusions were positively associated with verbal hallucinations and inversely associated with negative symptoms. In the healthy participants the extra-list intrusions were positively associated with proneness to hallucinations. A liberal response bias in the recognition of the high-frequency words was associated with verbal hallucinations in male patients and with proneness to hallucinations in healthy men. Meanwhile, a conservative response bias for these high-frequency words was associated with negative symptoms in male patients and with social anhedonia in healthy men. Conclusions: Misattribution of inner speech to an external source, reflected by false recollection of familiar material, seems to underlie both clinical and non-clinical hallucinations. Further, both clinical and non-clinical negative symptoms may exert on verbal memory errors an effect opposite to that of hallucinations.